Pengaruh Inovasi Produk Terhadap Keputusan Pembelian Konsumen pada Usaha Kreatif All Craftsupply Kota Jambi - Allfitri Raga Putti (Jurnal Dinamika Manajemen, 2020)
This study aims to analyze the effect of product innovation on consumer purchasing decisions in All craftssupply Creative Enterprises in the city of Jambi. The population in this study were consumers of All Crafts Supply Creative Enterprises with 75 respondents. The data collection technique used was a questionnaire. The analytical tool used in this study is the instrument test which consists of validity and reliability tests, multiple linear regression analysis, t test and coefficient of determination test. The entire analysis was calculated using the SPSS ver 22 program. The results of this study indicate that product innovation has a positive and significant effect on consumer purchasing decisions on All craftssupply Creative Enterprises in Jambi City.